Work that body: fin and body movements determine herbivore feeding performance within the natural reef environment. Issue 1938 (11th November 2020) - Perevolotsky, Tal; Martin, Christopher H.; Rivlin, Asaph; Holzman, Roi
Abstract : Herbivorous fishes form a keystone component of reef ecosystems, yet the functional mechanisms underlying their feeding performance are poorly understood. In water, gravity is counter-balanced by buoyancy, hence fish are recoiled backwards after every bite they take from the substrate. To overcome this recoil and maintain contact with the algae covered substrate, fish need to generate thrust while feeding. However, the locomotory performance of reef herbivores in the context of feeding has hitherto been ignored. We used a three-dimensional high-speed video system to track mouth and body kinematics during in situ feeding strikes of fishes in the genus Zebrasoma, while synchronously recording the forces exerted on the substrate. These herbivores committed stereotypic and coordinated body and fin movements when feeding off the substrate and these movements determined algal biomass removed. Specifically, the speed of rapidly backing away from the substrate was associated with the magnitude of the pull force and the biomass of algae removed from the substrate per feeding bout. Our new framework for measuring biting performance in situ demonstrates that coordinated movements of the body and fins play a crucial role in herbivore foraging performance and may explain major axes of body and fin shape diversification across reef herbivore guilds.